Providing for Future Change Adaptability and Flexibility in School Building. OECD Programme on Educational Building. - Organisation for Economic Cooperation and Development, Paris (France).; Organisation for Economic Cooperation and Development, Paris (France). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This publication discusses the need to design school buildings that are both flexible (i.e., responsive to frequent slight changes in use) and adaptable (i.e., responsive to infrequent major changes in use) and examines three actual school buildings that illustrate different approaches to achieving building flexibility and/or adaptability. Part 1 is a brief introductory section that describes the objectives and methodology of the study. Part 2 presents case examples of three schools of varying design and examines how each building might be adapted to accomodate alternative uses. Part 3 discusses the implications of providing for future change, including implications for institutional and managerial arrangements, implications for physical characteristics of the school, and cost implications of providing for building flexibility and adaptability. Part 4 presents a summary of the study's major conclusions. Each case example includes several floor plan diagrams that illustrate how the building might be used to serve a number of different educational objectives. (JG)
Availability: OECD Publications Center, Suite 1207, 1750 Pennsylvania Avenue, N.W., Washington, D.C. 20006 ($7.00).
ERIC Note: Floor plans and photographs will not reproduce clearly.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Building Design; Building Plans; Design Requirements; Educational Facilities; Elementary Secondary Education; Facility Case Studies; Facility Planning; Flexible Facilities; School Buildings; Reports, Research